Through-Hole Microwave Resonators for Magnonic Quantum Transducer - Yengejeh, Morteza Vafadar; Rameev, Bulat (Springer Wien, 2023)
For the realization of the quantum network, the coherent conversion from microwave to optical waves, and vice versa, plays a key role in connecting quantum computation or sensing components over long distances. To this end, one exciting approach is the hybrid system based on the use of the collective spin excitation (magnon) modes in a yttrium iron garnet (YIG) coupled to both microwave cavity mode and optical cavity mode. This system is actively researched toward increasing efficiency and bandwidth of conversion. There have been studies on the magnon-based hybrid systems in the planar geometry due to the possibility to enhance the coupling in the microwave-magnon subsystem and a need to develop solutions that are easier to implement in practice, especially for operation at low (ultra-low) temperatures. In this work, we propose and demonstrate microwave planar resonators with a thin film of YIG on top of a through-hole feature. The hole in the board of the microwave resonator provides perpendicular passage of the pumping and signal lights, enabling efficient coupling of external optical resonator modes with magnon modes. For this work, we concentrated only on the microwave-magnon subsystem of the proposed quantum hybrid system, although efficient coupling between all three parts (microwave cavity, magnon, and optical cavity) is planned to be realized. We achieve a microwave-magnon coupling strength of 448 MHz with a resonator having a circular hole of 1 mm diameter.